Evaluation of CORDEX ERA5-forced NARCliM2.0 regional climate models over Australia using the Weather Research and Forecasting (WRF) model version 4.1.2 - G. Di Virgilio; G. Di Virgilio; F. Ji; F. Ji; E. Tam; J. P. Evans; J. P. Evans; J. Kala; J. Andrys; C. Thomas; D. Choudhury; C. Rocha; et al. (Geoscientific Model Development)
Understanding regional climate model (RCM) capabilities to simulate current climate informs model development and climate change assessments. This is the first evaluation of the NARCliM2.0 ensemble of seven Weather Forecasting and Research RCMs driven by ECMWF Reanalysis v5 (ERA5) over Australia at 20 km resolution contributing to CORDEX-CMIP6 Australasia and southeastern Australia at convection-permitting resolution (4 km). The performances of these seven ERA5 RCMs (R1–R7) in simulating mean and extreme maximum and minimum temperatures and precipitation are evaluated against observations at annual, seasonal, and daily timescales and compared to corresponding performances of previous-generation CORDEX-CMIP5 Australasia ERA-Interim-driven RCMs. ERA5 RCMs substantially reduce cold biases for mean and extreme maximum temperature versus ERA-Interim RCMs, with the best-performing ERA5 RCMs showing small mean absolute biases (ERA5-R5: 0.54 K; ERA5-R1: 0.81 K, respectively) but produce no improvements for minimum temperature. At 20 km resolution, improvements in mean and extreme precipitation for ERA5 RCMs versus ERA-Interim RCMs are principally evident over southeastern Australia, whereas strong biases remain over northern Australia. At convection-permitting scale over southeastern Australia, mean absolute biases for mean precipitation for the ERA5 RCM ensemble are around 79 % smaller versus the ERA-Interim RCMs that simulate for this region. Although ERA5 reanalysis data confer improvements over ERA-Interim, only improvements in precipitation simulation by ERA5 RCMs are attributable to the ERA5 driving data, with RCM improvements for maximum temperature being more attributable to model design choices, suggesting improved driving data do not guarantee all RCM performance improvements, with potential implications for CMIP6-forced dynamical downscaling. This evaluation shows that NARCliM2.0 ERA5 RCMs provide valuable reference simulations for upcoming CMIP6-forced downscaling over CORDEX-Australasia and are informative datasets for climate impact studies. Using a subset of these RCMs for simulating CMIP6-forced climate projections over CORDEX-Australasia and/or at convection-permitting scales could yield tangible benefits in simulating regional climate.